Interactive Voice Response and Text-based Self-report Versions of the Electronic Columbia-Suicide Severity Rating Scale Are Equivalent - Gwaltney, Chad (Innov Clin Neurosci, 2017)
Objectives: Our study objective was to compare the equivalence of a new version of the electronic Columbia-Suicide Severity Rating Scale that was administered on a tablet device with the existing interactive voice response version in order to support the prospective monitoring of suicidal ideation and behavior in clinical trials and clinical practice. Design: This was a randomized, crossover-equivalence study with no treatment intervention. Setting: The study setting was a psychiatric hospital. Participants: Fifty-eight recently admitted psychiatric inpatients and 28 employees of the hospital site were included in the study. Mean age was 41.0 years (standard deviation=12.5), and 59 percent were female. Measurements: Participants completed both tablet and interactive voice response versions in randomized order, with a 25-minute break between administrations. Finally, participants completed a second administration of the first administered version. Intraclass correlation coefficients (ICCs) and Kappa coefficients were used to evaluate agreement across modalities. Results: High levels of agreement were observed for most severe lifetime (ICC=0.88) and recent (ICC=0.79) ideation, occurrence of actual lifetime (Kappa=0.81) and recent (Kappa=0.73) suicide attempts, and occurrence of lifetime interrupted attempts (Kappa=0.78), aborted attempts (Kappa=0.54), and preparatory behaviors (Kappa=0.77), as well as non-suicidal self-injurious behavior (Kappa=0.73). Scores from both modes significantly differentiated psychiatric patients and hospital employee controls, and the test-retest reliability of both modes was excellent. Conclusions: These results support the validity and reliability of the new tablet-based electronic Columbia-Suicide Severity Rating Scale. This will allow the inclusion of the electronic Columbia-Suicide Severity Rating Scale in a wider range of clinical studies, particularly where a tablet is also being used to collect other study data.